TASCHEN's London : hotels, restaurants & shops - Taschen, Angelika, ....-; Samuelian, Christine, ....-; Crookes, David, ....- (Los Angeles : TASCHEN America, 2009)
From Dickensian charm to modern cool, London has it all–and this guide will help you find it. With a selection of stylish hotels, from classic to designer; antique markets, vintage stores and the hippest boutiques; and all the best of the capital's restaurants, bars, tea rooms and pubs, Angelika Taschen's compact compendium is a must for the discerning traveller. Highlights include Number Sixteen, a chic South Kensington hotel in a beautiful Victorian townhouse with romatic gardens; The Wolseley, a grand café and restaurant in a reconverted 1920s car showroom beautifully renovated by star designer David Collins; celebrity chef Jamie Oliver's restaurant and social project, Fifteen, where teenagers cook the meals; China Tang at The Dorchester, where stars go for delectable duck with plum sauce; historic London pub, The Grenadier, once frequented by the Duke of Wellington's troops; Dover Street Market, the multi-floor concept store founded in 2004 by Comme des Garçons; and Penhaligon's, purveyors of classic English fragrances since 1872.
Keywords: Hotels London; Restaurants London; Winkels Londen